al-zakāh wa al-Ḍarībah fi al-Fiqh al-Islāmī wa al-qānūn al-Indūnīsī (Dirāsah Tajrībiyyah Muqāranah) - Ahmad Muqorobin (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2020)
Zakat is a financial system that is essential to create a balance between society, so as not to make the rich richer and vice versa.Zakat is an obligation for Muslims to get closer to Allah and to cleanse his property. While the tax is a mandatory contribution to the state charged to the public for the benefit of the government and the general public. Seeing the importance of zakat and tax as an instrument of income of a country, then the purpose of this study was to determine the legitimacy of a combination of zakat and taxation in Islamic law, and its application in Indonesia, whose population includes Muslims and non-Muslims. This research uses descriptive analysis approach and simultaneously inductive approach in explaining the rules of zakat and tax system and to clarify the differences between them, then explain the application of zakat and taxation in Indonesia, for increasing the zakat payment.